(untitled) (Natural Resources and Technology, 2016)
Fires, often taking away human lives and causing huge material damage,regardless of their background. In this paper we will explain in detail one ofthe newer methods for ires troubleshooting that is ires extinguishing withaerosols generated by solid substances. The purpose of this paper is to showeffectiveness and feasibility of applying this method for human, natural andmaterial goods protection. Necessity оf this ire protection kind in industrialfacilities will be particularly emphasized.